2007
DOI: 10.1590/s0100-879x2007000400015
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of CD4+ T cells to the early mechanisms of ischemia- reperfusion injury in a mouse model of acute renal failure

Abstract: Renal ischemia-reperfusion (IR) injury is the major cause of acute renal failure in native and transplanted kidneys. Mononuclear leukocytes have been reported in renal tissue as part of the innate and adaptive responses triggered by IR. We investigated the participation of CD4 + T lymphocytes in the pathogenesis of renal IR injury. Male mice (C57BL/6, 8 to 12 weeks old) were submitted to 45 min of ischemia by renal pedicle clamping followed by reperfusion. We evaluated the role of CD4 + T cells using a monoclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 36 publications
0
19
0
1
Order By: Relevance
“…It is generally agreed that trauma suppresses CD4 + T-cell responses (54,83,124,159). For example, Th1-type immune responses have been shown to be reduced markedly following trauma in patients and in mouse injury models (42,73,104).…”
Section: Nitric Oxidementioning
confidence: 99%
“…It is generally agreed that trauma suppresses CD4 + T-cell responses (54,83,124,159). For example, Th1-type immune responses have been shown to be reduced markedly following trauma in patients and in mouse injury models (42,73,104).…”
Section: Nitric Oxidementioning
confidence: 99%
“…This becomes even more important when recent studies have suggested that there are no patient and graft survival differences between kidney transplant recipients on steroids and azathioprine/tacrolimus or mycophenolate/tacrolimus regimens, pointing to azathioprine as a therapeutic option for selected patients ( Figure 12). 54 advances in the understanding of the molecular and cellular mechanisms involved in the ischemia and reperfusion injury, [55][56][57] and in human operational tolerance. 58 peRspectives Brazil has experimented advances in its social organization, which can be evidenced by an increased life expectation at birth (76 years for women and 69 years for men), 59 a decreased birth rate (reduced from 5.6 to 2.1 in the past 30 years), 60 reduced infant mortality rate, and reduced urban violence and number of violent deaths (from 13,257 in 1999 to 4,436, in 2007, in São Paulo).…”
mentioning
confidence: 99%
“…It was demonstrated that reactive oxygen species (ROS) and reactive nitrogen species (RNS) increase in the areas of ischemia and reperfusion, which are responsible for renal damage. Inflammation also plays an important role in the pathogenesis of renal I/R injury, through leukocyte activation and expression of adhesion molecules and cytokines [1][2][3][4][5][6] . Free radicals and pro-inflammatory cytokines can damage cellular membrane and subcellular structures, which contain large amounts of phospholipids and protein, resulting in lipid peroxidation and sequentially structural and IJBAR (2012) 03(07) www.ssjournals.com metabolic alterations, leading to cell apoptosis and necrosis.…”
Section: Introductionmentioning
confidence: 99%